Women's empowerment in agriculture and household food insecurity: Evidence from Azad Jammu & Kashmir (AJK), Pakistan. (March 2021) - Aziz, Noshaba; Ren, Yanjun; Rong, Kong; Zhou, Jin
Highlights: The study portrays the empowerment of women in agriculture and its influence on household food insecurity. A woman empowered in production, resources, leadership and time domain improves household food security. The income domain unexpectedly disrupts the householdfood security. The results direct policy makers to take into account some non-economic factors such as cultural norms etc. The cultural norms may limit women's control over income and eventually their access to buy food. Abstract: Despite the extensive literature on women's empowerment, the measurement of empowerment in the agricultural context is limited, especially in Pakistan. In this study, we used the Women's Empowerment in Agriculture Index (WEAI) to explore its effect on household food insecurity in the northern part of AJK, Pakistan, using household survey data of 600 rural women. By using the Partial Least Square model structural equation model (PLS-SEM), the outcomes show that rights of women in the leadership domain, agricultural production domain, resource ownership in the form of land and livestock and time-domain i.e., time spent on farming lands have significant negative effects on food insecurity, i.e., women can improve the vulnerability of their households by having access to these rights. Surprisingly, we found that women's empowerment in the income domain provides significant but positive results, which points out that some non-economic mechanisms such as patriarchal customs and norms may prevent women from controlling their household income. As a consequence, women are likely to spend less money on accessing foods. The study results have significant implications for developmental practitioners targeting alleviating food insecurity, and empowering women must focus on cultural factors.